Relationship of Bacterial Richness to Organic Degradation Rate and Sediment Age in Subseafloor Sediment - Walsh, Emily A. (Appl Environ Microbiol, 2016)
Subseafloor sediment hosts a large, taxonomically rich, and metabolically diverse microbial ecosystem. However, the factors that control microbial diversity in subseafloor sediment have rarely been explored. Here, we show that bacterial richness varies with organic degradation rate and sediment age. At three open-ocean sites (in the Bering Sea and equatorial Pacific) and one continental margin site (Indian Ocean), richness decreases exponentially with increasing sediment depth. The rate of decrease in richness with increasing depth varies from site to site. The vertical succession of predominant terminal electron acceptors correlates with abundance-weighted community composition but does not drive the vertical decrease in richness. Vertical patterns of richness at the open-ocean sites closely match organic degradation rates; both properties are highest near the seafloor and decline together as sediment depth increases. This relationship suggests that (i) total catabolic activity and/or electron donor diversity exerts a primary influence on bacterial richness in marine sediment and (ii) many bacterial taxa that are poorly adapted for subseafloor sedimentary conditions are degraded in the geologically young sediment, where respiration rates are high. Richness consistently takes a few hundred thousand years to decline from near-seafloor values to much lower values in deep anoxic subseafloor sediment, regardless of sedimentation rate, predominant terminal electron acceptor, or oceanographic context. IMPORTANCE Subseafloor sediment provides a wonderful opportunity to investigate the drivers of microbial diversity in communities that may have been isolated for millions of years. Our paper shows the impact of in situ conditions on bacterial community structure in subseafloor sediment. Specifically, it shows that bacterial richness in subseafloor sediment declines exponentially with sediment age, and in parallel with organic-fueled oxidation rate. This result suggests that subseafloor diversity ultimately depends on electron donor diversity and/or total community respiration. This work studied how and why biological richness changes over time in the extraordinary ecosystem of subseafloor sediment.